2020
DOI: 10.11591/edulearn.v14i4.16429
|View full text |Cite
|
Sign up to set email alerts
|

Mini-seminar project: An authentic assessment practice in speaking class for advanced students

Abstract: This paper reports one best-practice in assessing the public speaking performance of advanced students at an Indonesian public university. The study involves an English course for an advanced class which was primarily related to public speaking skills. Considering that speaking is a productive skill that should be assessed through authentic assessment principles, the lecturers decided to assign the students with a mini-seminar project as part of their final examination. This project required the students to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…It showed that authentic assessment was so necessary to measure students' ability in learning English. In line with this research finding, Daud et al, (2020) also found that an appropriate way of teaching speaking can improve students' speaking ability. Besides, Putri et al, (2021) described the application of authentic assessment done by English teachers in online learning.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…It showed that authentic assessment was so necessary to measure students' ability in learning English. In line with this research finding, Daud et al, (2020) also found that an appropriate way of teaching speaking can improve students' speaking ability. Besides, Putri et al, (2021) described the application of authentic assessment done by English teachers in online learning.…”
Section: Introductionsupporting
confidence: 77%
“…Based on the subject of the research, Junaedi (2019) chosen English lecturers as the source of data and Daud et al (2020) invited an English course to participate in the research. In order to find the result, Daud et al (2020) utilize an activity named a seminar. The finding also different from Putri et al, (2021).…”
Section: Discussionmentioning
confidence: 99%
“…Authentic assessment is a term that is frequently used to describe non-test forms of evaluation. like what was carried out by (Daud et al, 2020); (Kamarudin et al, 2020); and (Bock et al, 2020).…”
Section: Introductionmentioning
confidence: 65%
“… Before the Webinar is done, the researchers and instructors create an evaluation rubric. The of the evaluation rubric was adapted from a previously produced rubric (Daud et al, 2020).…”
Section: Figure 1 Instructions On Google Classroommentioning
confidence: 99%
“…Furthermore, assessment can be in the form of tests and non-tests. The assessment in the form of tests usually appears in the form of objective tests, written tests, and oral tests, while nontests one can be done in various forms, such as observation, performance, assignments, presentations, seminars, and other authentic forms (Daud et al, 2020).…”
Section: Literature Review Assessment In Educationmentioning
confidence: 99%